Tendoscopic treatment of acute posterior tibial tendon dysfunction: case report - Saraiva, Daniel; Knupp, Markus; Rodrigues, André Sá; Gomes, Tiago Mota; Oliva, Xavier Martin (Journal of the Foot & Ankle, 2021)
We present a case of a rheumatoid patient presenting with acute signs of posterior tibial tendon dysfunction (PTTD). Magnetic resonance imaging (MRI) results were inconclusive regarding the grade of posterior tibial tendon (PTT) tear. We performed posterior tibial tendoscopy, releasing all tendon adherences, and accomplished complete synovectomy. By the end of the procedure, we observed PTT integrity, normal excursion, and mild tendinosis. At 24-month follow-up, the Visual Analog Scale for pain (VAS-Pain) decreased from 9 (preoperatively) to 1. The Foot and Ankle Outcome Score (FAOS) increased from 16% (preoperatively) to 94%. Clinically, the patient had a symmetric bilateral heel rise test and no pain over the course of the PTT. A standard radiographic assessment demonstrated a normal foot arch and hindfoot alignment. This report illustrates how posterior tibial tendoscopy can simultaneously provide accurate diagnosis and surgically address acute PTTD on a rheumatoid patient, relieving symptoms and improving midterm clinical scores. Level of Evidence V; Therapeutic Studies; Expert Opinion.